Cryoprotective Potential of Lecithins in Optimizing Pork Mince Functionality - Mostowski, Radosław (Wydawnictwo Politechniki Łódzkiej, 2025)
The negative effects of meat freezing, associated with the phase transition of water into ice, primarily involve changes in the physicochemical properties of myofibrillar proteins, which are responsible, among other functions, for water retention. These adverse effects can be mitigated through the use of cryoprotectants. We investigated the cryoprotective properties of lecithin, depending on its type (soybean, rapeseed, sunflower) and form (powder, deoiled, liquid), at concentrations ranging from 0.5% to 10%. Our findings suggest that lecithin powders derived from soybeans, rapeseed, and sunflower may serve as effective cryoprotectants for frozen pork ham during freezing. The optimal concentration of these cryoprotectants was found to be 2.5%. Lecithin powder additives positively influenced the technological properties of meat proteins by increasing both the denaturation temperature and the glass transition temperature. Furthermore, lecithin helped maintain protein solubility and enhanced the meat's water-holding capacity. Its use also improved the nutritional profile of the meat by increasing the content of polyunsaturated fatty acids, particularly α-linolenic acid from the omega-3 family.
Keywords: minced pork; frozen meat; meat cryoprotectants; lecithin; pork meat